Rancang Bangun Sistem Monitoring Kebun Menggunakan Sensor PIR dan ESP32-Cam Berbasis IoT - Leonard Maramis; Chandra Nugroho; Husna Saleh; Ridwan Potabuga; Varly Carnavale Wullur (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
Abstract: This research focuses on the development of an Internet of Things (IoT)-based garden monitoring system designed to assist in the automatic supervision of plantation areas. The problem addressed is the difficulty in detecting the movement of pest animals in real time; therefore, this study aims to build a system capable of detecting, recording, and sending rapid movement notifications to users via a Telegram BOT. The method used is an experimental approach involving the design and testing of a system consisting of an ESP32 microcontroller as the control center, a Passive Infrared (PIR) sensor as a motion detector, an ESP32-Cam module as an image capture device, and a buzzer as an audio indicator. The research results show that the developed system works effectively in detecting the movement of animals or other objects, automatically capturing images, and transmitting monitoring results in real time through Telegram. The synthesis of these findings indicates that the integration of PIR sensors and ESP32-Cam provides an efficient solution for IoT-based garden security systems. It is concluded that this system not only improves the effectiveness of garden monitoring but also has potential for further development in terms of accuracy, detection intelligence, and integration with other monitoring systems.